QUESTIONNAIRE OF SOCIAL PROBABILITY AND POTENTIAL CONSEQUENCES – EXAMINATION OF RELIABILITY AND VALIDITY ON SERBIAN POPULATION - Ranđelović, Kristina M.; Ranđelovic, Dušan J. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
Prejudice in judgment has an important role in cognitive models of psychopathology. Every selective processing of emotionally relevant stimuli is called cognitive prejudice. One of the cognitive prejudices that is considered a key factor of socially – anxious disorder is prejudice in judgment. It is defined as a disposition to overestimate the probability of occurrence of negative social events in the near future, as well as potential consequences (agitation) that might follow them. The perception of danger is essentially determined by a joined effect of subjective assessment of probability and agitation created by certain events. The researches have shown that socially-anxious individuals have a more expressive prejudice in judgment and that it can be reduced by applying certain psychotherapeutic and pharmacological treatments, which proves its relevance for the socially-anxious disorder. Considering the significance of the prejudice in judgment construct for the research and clinical practice and the lack of instruments that is operational in our country, the basic purpose of this paper is to check metric characteristics of the Serbian version of one of the most often mentioned and used questionnairesaimed at the assessment of this construct. It is the Questionnaire of social probability and potential consequences, which has two subscales: 1) to examine the reliability of the questionnaire on the sample of examinees from Serbia; 2) to examine the latent structure of the questionnaire and 3) to examine the construct of validity of the questionnaire by checking the correlations with other relevant constructs (personality traits, anxiety as a trait and fear of negative evaluation).The was adapted for Serbian language from English. The sample consists of 166 examinees, aged from 19 to 29 (AS = 21,73; SD = 1,43). The questionnaire for sensitivity to confirmation assessment was used to estimate personality traits, Anxiety as a trait was estimated by the Scale of anxiety as a trait, which is a part of the anxiety as a trait and condition Inventory, and fear of negative evaluation was estimated by the Scale of fear of negative evaluation – short form. The results show that the instrument for evaluation of prejudice in judgment is highly reliable (α=.96; α=.96), and taht its items can be considered representative (KMO = .93; KMO = .93) and homogeneous (h1 = .47; h1 =.44). In the purpose of the assessment of the latent structure of the questionnaire an explorational factor analysis was conducted (the methods of the main components), and the results suggested that the questionnaire is the kind with two one-dimension subscales (the pecentage of the explained variance is 49.21% i 45.80%). In favor of the construct of validity are the results of correlation analysis, that describe important relations of both components of prejudice in jugdment with personality traits, anxiety and fear of negative evaluation, and they do so in the expected direction. In accordance with all this, the serbian version of the questionnaire can be recomended for measuring prejudice in judgment